Study of in-vitro aqueous re-dispersibility of inhaled nanoparticulate aggregates. - Lie, Ru Hui. (2010)
The use of nanoparticles as drug carriers for pulmonary delivery of medicines is advantageous as they are able to remain in the lung for sustained periods of time. Nanoparticles loaded with Levofloxacin (LEV) were prepared using the emulsification-solvent-evaporation (ESE) method. Development and optimization of this method was done by varying the concentration of polyvinyl alcohol (PVA) in the external aqueous phase, the sonicating amplitude and time. A range of nanoparticle sizes from 190 to 400 nm was produced. Re-dispersible characterization was then done on nanoparticle aggregates produced by a novel spray-freeze drying (SFD) method. Increasing the ratio of excipients (mannitol and PVA) in the SFD formulation improved the re-dispersibility of the aggregates. This was observed by the decrease in the size ratio of the reconstituted particles. A value nearer to 1 would mean that the size is closer to that of the original nanoparticles. An increasing percentage of nanoparticulate aggregates were able re-disperse into this size. Aggregates spray-freeze dried with PVA was observed to have a higher drug loading than those with mannitol. The aggregates spray-freeze dried with PVA displayed better re-dispersibility characteristics.